Organogenesis in okra (Abelmoschus esculentus L. Moench.): A plant recalcitrant to tissue culture (Bangladesh Journal of Agricultural Research, 2016)
Seedling-derived cotyledonary nodes and hypocotyl explants of BARI Dherosh- 1 were cultured in vitro on MS medium supplemented with varying concentrations of 2, 4-Dichlorophenoxy acetic acid (2, 4-D), 6- Benzylaminopurine (BAP), Thidiazuron (TDZ), BAP with 1-Nepthaleneacetic acid (NAA), BAP with Indole 3-butyric acid (IAA) and Zeatin with IAA along with a control. Shooting response (100%) with callus was only observed from cotyledonary nodes on thidiazuron (TDZ) where hypocotyls produced only callus or callus with roots on different concentrations of plant growth regulators. Considering the shooting response, the cotyledonary nodes of BARI Dherosh-1 were cultured on various concentrations of TDZ for regeneration. The highest percentage (64.0) with maximum number (6.8) of shoots per explant were observed in 0.044 ?M TDZ in 8.4 days. The regenerated shoots were rooted on ½ strength MS, MS supplemented with 2.46 ?M IBA and 0.53 ?M NAA. The highest percentage (83.3) and minimum days (9.7) required for root induction were recorded in 2.46 ?M IBA. The rooted plantlets were transferred to soil and hardened in the plastic pots under green house conditions. The rooted shoots grew normally under natural conditions following acclimatization.Bangladesh J. Agril. Res. 41(3): 521-528, September 2016